A NEW SPECIES of THE BOKERMANNOHYLA MARTINSI GROUP FROM CENTRAL BAHIA, BRAZIL WITH COMMENTS on BOKERMANNOHYLA (ANURA: HYLIDAE) - Faivovich, Julian [UNESP]; Lugli, Luciana; Calijorne Lourenco, Ana Carolina; Haddad, Celio Fernando Baptista [UNESP] (Herpetologists League, 2009)
A new species of the Bokermannohyla martinsi group is described from Chapada Diamantina, State of Bahia, northeastern Brazil. It is differentiated from the other two species in the group by the combination of slender body (quite robust in B. langei and B. martinsi), non-bifid distal prepollex (bifid in B. langei and B. martinsi), squared shape of the posterior portion of the distal prepollex (pointed process in B. langei and B. martinsi), large size and lateral inclination of the tympanum (quite reduced in B. langei, almost parallel to the longitudinal axis in both B. langei mid B. martinsi), absence of dark bars in hidden areas of thighs (dark bars present oil anterior, dorsal and posterior surfaces of thighs ill B. martinsi), and shape of the supratympanic fold. We report for the first time the occurrence of a mental gland 16 species of Bokermannohyla.
Keywords: Amphibia; Bokermannohyla juiju; Cophomantini; Hylidae; Mental gland; Taxonomy